Reaction of complement factors varies with prion strains in vitro and in vivo - Hasebe, Rie (2012)
Roles of complement factors in prion infection of the central nervous system remain unclear. In this study, we assessed the strain-dependent reactivity of complement factors in prion infections of Neuro2a (N2a) cells and mouse brains. N2a cells persistently infected with either Chandler or 22L scrapie strains were cultured in the presence of normal mouse serum (NMS), followed by staining with the phosphatidylserine binding protein and early apoptosis marker Annexin V. The proportion of Annexin V positive cells was increased both in Chandler- and 22L-infected cells. Preincubation of NMS with anti-C1q, C3 and/or C9 antibodies reduced Annexin V positive cells in Chandler-infected cells, while only anti-C3 antibodies were effective on 22L-infected cells. The immunohistochemistry showed that deposition of C1q and C3 was different between Chandler- and 22L-infected mouse brains. These results indicate that the reactivity of complement factors differs between prion strains both in vitro and in vivo.